(untitled) (Research, Society and Development, 2020)
The present study aimed to conduct an integrative review on the influence of consumption of processed foods on overweight and childhood obesity. The search sources were the databases: Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Google Scholar, they are online search platforms. To perform the search, the following descriptors registered in the descriptors in health sciences (DeCS) were used: “Ultra-processed foods”, “Childhood obesity” and “Children”. To select the sample, the following inclusion criteria were used: Original articles published from 2014 to 2020, indexed in the selected databases. it was observed that the consumption of processed foods prevails, showing the consequences of their intake on children’s health, including weight gain, dyslipidemia and metabolic syndrome. The studies already carried out allow the obtaining of relevant information regarding the contribution of correct eating habits, where we observed some of the many foods that are factors of great influence for the high levels of weight gain and chronic diseases, not only for a good development, but also, to make these children healthy adults. In view of the various researched studies, it is possible to verify that overweight and childhood obesity are starting more and more early, as well as having a strong influence with the consumption of processed foods.